The Cosmic Microwave Background - Jones Aled; Lasenby Anthony (Living Reviews in Relativity, 1998)
We present a brief review of current theory and observations of the cosmic microwave background (CMB). New predictions for cosmological defect theories and an overview of the inflationary theory are discussed. Recent results from various observations of the anisotropies of the microwave background are described and a summary of the proposed experiments is presented. A new analysis technique based on Bayesian statistics that can be used to reconstruct the underlying sky fluctuations is summarised. Current CMB data is used to set some preliminary constraints on the values of fundamental cosmological parameters $Omega$ and $H_circ$ using the maximum likelihood technique. In addition, secondary anisotropies due to the Sunyaev-Zel'dovich effect are described.